2014
DOI: 10.1001/jamaoto.2014.1258
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Head and Neck Cancer in Patients With Diabetes Mellitus

Abstract: Diabetes is associated with an increased risk of developing HNC. The risks of developing oral cavity cancer, oropharyngeal cancer, and nasopharyngeal carcinoma were significantly higher in patients with DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 45 publications
2
32
0
1
Order By: Relevance
“…The comparison non-DM cohort was 1-to-1 matched with the DM cohort by age, sex, index date, and comorbidities with a minimum 2 visits. [ 23 ] The comorbidities included coronary artery disease (CAD) (410–414, A270, and A279), hyperlipidemia (272), hypertension (401–405), chronic kidney disease (CKD) (585), chronic obstructive pulmonary disease (COPD) (490–496, a surrogate for smoking), and obesity (278.0 and V778). The immunosuppression status is also an important risk factor of skin cancer.…”
Section: Methodsmentioning
confidence: 99%
“…The comparison non-DM cohort was 1-to-1 matched with the DM cohort by age, sex, index date, and comorbidities with a minimum 2 visits. [ 23 ] The comorbidities included coronary artery disease (CAD) (410–414, A270, and A279), hyperlipidemia (272), hypertension (401–405), chronic kidney disease (CKD) (585), chronic obstructive pulmonary disease (COPD) (490–496, a surrogate for smoking), and obesity (278.0 and V778). The immunosuppression status is also an important risk factor of skin cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Second, lifestyle information such as consumption, smoking habit, betel nut chewing, dietary habits, and data of family history was lacking in the present study and might have some bias. However, based on Yeh 38 and Tseng's 39 studies, we added the adjustment of smoking-related disease and the alcohol-related diseases to reduce smoking and alcoholism related confounder. Third, based on ICD-9 code, we cannot distinguish histologic types of cancer.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Three studies were conducted in Southeast Asia, and one in Europe. Matched design was introduced in two studies, 16 , 18 and three studies used multivariate analysis to calculate ORs. 16 18 Hsieh et al reported ORs from three subgroups instead of the whole cohort.…”
Section: Resultsmentioning
confidence: 99%